A Mythical Animal Codification in Wish Dragon 2021 - Adrio, May Lita Dinda; Purnomosasih, Lusia Kristiasih Dwi (Universitas PGRI Madiun, 2024)
The purpose of this research is to find out the manifestation of Chinese dragon in movies. In this research, the researcher used the theory of popular literature by Simon (2000), and cinematic representation by Stuart Hall (1989). The research method used is a qualitative descriptive method with data collection techniques using documentation techniques and then analyzed using analytical techniques by Ary, D., Jacobs, L. C., & Sorensen, C. K. (2010). The result of the research is, the depiction of dragons in various movies is depicted differently due to historical and cultural influences. The differences are also made to construct a reality that the movie maker wants to show. Even though the dragons in movies are depicted differently, the shape of the dragon still adheres to the general form of the Chinese dragon